Correlation of low field nuclear magnetic resonance relaxation with composition and glass transition of hard candies - Ozel, Baris; Berk, Berkay; Uguz, Sirvan Sultan; Grunin, Leonid; Oztop, Mecit Halil (Frontiers in Food Science and Technology, 2024)
Hard candies produced from sucrose and doctoring agents such as glucose syrup (GS) and high fructose corn syrup (FS) have been investigated in terms of their final composition, glass transition temperature (Tg), degree of crystallinity, total soluble solids (TSS) content and water activity (aw). Time domain (TD) 1H NMR longitudinal relaxation time (T1) and second moment (M2) measurements have been used to understand the glassy state and crystallization characteristics for different hard candy formulations. The investigated candies include sucrose as the main sugar component. Different levels of doctoring agents have been mixed with sucrose to obtain products with different characteristics. It has been shown that addition of any doctoring agent to sucrose formulations decreases the Tg of the system significantly (p≤ 0.05). Furthermore, GS or FS addition also induce significant changes in TSS and aw. T1 and M2 results are almost parallel to each other, both reaching the highest values for the highest sucrose concentration (p≤ 0.05). The results demonstrate that the glass transition and crystallization characteristics of hard candy formulations can be monitored and analyzed by TD NMR relaxometry, alternative to other frequently used conventional methods including differential scanning calorimetry (DSC) and X-ray diffraction.